2013
DOI: 10.3109/03639045.2013.819884
|View full text |Cite
|
Sign up to set email alerts
|

Formulation by design of felodipine loaded liquid and solid self nanoemulsifying drug delivery systems using Box–Behnken design

Abstract: This study indicates that owing to nanosize, SNEDDS and S-SNEDDS of FLD have potential to enhance its absorption and may serve an efficient oral delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 36 publications
0
22
0
3
Order By: Relevance
“…Statistically, the responses were precisely described by the respective models evidenced with the F value of 17.12 (p50.05) and 9.99 for Flux-Span 60 and % EE-Span 60, respectively (Verma et al, 2014). These equations clearly indicated that the Flux-Span 60 and % EE-Span 60 were significantly affected with the concentration of B for flux (p50.0006) and % EE (p50.002), respectively.…”
Section: Preparation Of Elastic Liposomes and Optimizationmentioning
confidence: 60%
“…Statistically, the responses were precisely described by the respective models evidenced with the F value of 17.12 (p50.05) and 9.99 for Flux-Span 60 and % EE-Span 60, respectively (Verma et al, 2014). These equations clearly indicated that the Flux-Span 60 and % EE-Span 60 were significantly affected with the concentration of B for flux (p50.0006) and % EE (p50.002), respectively.…”
Section: Preparation Of Elastic Liposomes and Optimizationmentioning
confidence: 60%
“…Zeta potential was determined without dilution using a 4.0 mW He-Ne red laser (633 nm) to measure the surface charge from −120 to 120 mV. 20 The pH values of all formulations were determined using an HI 9321 pH meter (an electrode meter) (Hanna Instruments, Ann Arbor, MI, USA).…”
Section: Characterization Of Nanoemulsionsmentioning
confidence: 99%
“…The optimization design of CUR-CNLC and the data were analyzed by Design-Expert software (8.06 version, Stat Ease, Inc., Minneapolis, U.S.) [31]. The results were presented as the mean ± standard deviation (SD).…”
Section: Discussionmentioning
confidence: 99%